Pengaruh Kesadaran Pajak, Pemahaman Pajak, Pendapatan, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan Orang Pribadi di Kabupaten Magelang - Nina Purwaningsih; Chaidir Iswanaji; Riswa Wira Bharata (Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this study is to determine the effect of Tax Awareness, Tax Understanding, Income, and Tax Sanctions on the Compliance of Individual Land and Building Taxpayers in the Magelang Regency. The research method used is quantitative. The data in this study used primary data obtained from the distribution of questionnaires using a Likert measurement scale. The sampling technique used was purposive sampling with the criteria of the object of research being the people in Magelang Regency as land and building taxpayers. The results of this study indicate that tax awareness has a positive and significant effect on land and building taxpayer compliance, tax understanding has no significant effect on land and building taxpayer compliance, income has a positive and significant effect on land and building taxpayer compliance, and tax sanctions have an effect on significant negative impact on compliance with land and building tax payers. Simultaneously, the variables of tax awareness, tax understanding, income, and tax sanctions have a significant effect on the compliance of individual land and building taxpayers in Magelang Regency. Keywords: Tax Awareness, Tax Understanding, Total Income, Tax Sanctions, and Compliance of Individual Land and Building Taxpayers